Use of e-Cigarettes and Attendance at Stop Smoking Services: A Population Survey in England - Greg Hartwell; Matt Egan; Jamie Brown; Triantafyllos Pliakas; Mark Petticrew (Toxics, 2022)
Little is known about whether e-cigarette use influences tobacco smokers’ decisions around other smoking cessation options, including the most effective one available: stop smoking service (SSS) attendance. Our repeat cross-sectional survey therefore assessed associations between use of e-cigarettes with past and planned future uptake of SSSs. Nicotine replacement therapy (NRT) use was also assessed as a comparator. Participants were drawn from the Smoking Toolkit Study, a nationally representative, validated, face-to-face survey. Data were aggregated on 2139 English adults reporting current smoking of cigarettes or other tobacco products. Multivariable logistic regression was used to adjust for potential confounders. Results showed dual users of combustible tobacco and e-cigarettes were more likely than other smokers to report having accessed SSSs in the past (AOR 1.43, 95% CI 1.08 to 1.90) and intending to take up these services in future (AOR 1.51, 95% CI 1.14 to 2.00). Dual users of combustible tobacco and NRT showed similar associations. Secondary objectives provided evidence on key psychosocial factors that influenced smokers’ decision-making in this area. In summary, despite speculation that e-cigarette use might deter smokers from accessing SSSs, our study found dual users of tobacco and e-cigarettes were more likely to report uptake of such services, compared to smokers not using e-cigarettes.